IJCM_371A: Patterns of patient self-identification of ailments: A cross-sectional study from tertiary care centers in Mangalore - Rekha T; Menon Lakshmi; Sinnaswamy Ajay; Sarkar Ravishankar; Nambiar Pooja; Patoary Tapendu; Unnikrishnan Bhaskaran; Mithra Prasanna; Kumar Nithin; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: Self-diagnosis is the process of determining a disease or disorder without seeking medical care. Advances in technology have made it easier for patients to get medical information online, fostering self-diagnosis and doctor cross-examination. The aim of this study is to estimate the proportion of study respondents who use the internet and other sources for self-diagnosis and explore their attitudes concerning self-diagnosis. Methodology: This cross- sectional study was conducted among 186 participants from hospitals affiliated to Kasturba Medical college, Mangalore (Govt Wenlock hospital and KMC Hospital, Attavar). The data was collected using a semi-structured, internally validated questionnaire- consisting of 3 sections: 1) General information of study participants 2A) Questions on self- diagnosis through different sources 2B) On their attitudes concerning self-diagnosis. Data was analyzed using SPSS version 24. Results were expressed in descriptive statistics. Results: This study on self-diagnosis was conducted among OPD attendees and found a mean age of 31 years, with 66.0 % males and 34.0 % females. Majority (98.4%) had media access, in which 67.7% online media for self-diagnosis. Specific diseases like cancer and infectious disease were common search topics (76.3%). One third of the total participants reported they have done online search for ailments related to their relatives or friends. Around 61.3% considered their sources reliable, while 50.5% intended to continue self-diagnosing. Notably, 61.3% made correct self- diagnoses which were confirmed later after the physical consultation with their treating physician, particularly among participants under 25 with higher education. Conclusion: Due to the development of artificial intelligence and internet access, even non-medical people are now searching the media for medical issues. Although there is a growing dependence on internet resources, most individuals still say they trust in future self-diagnosis but still prefer visiting a doctor rather than self-medicating. To educate the public about the risks associated with self-diagnosis and the purchase of over-the-counter medications, community-based behavioral change communication should be employed.